2011
DOI: 10.1111/j.1447-0756.2010.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Is laparoscopic surgery safe in women over 70 years old with benign gynecological disease?

Abstract: Laparoscopic surgery in elderly women for benign gynecological disease is feasible, efficient, and safe. However, a large prospective randomized study is needed to confirm the conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Laparoscopic surgery for benign gynecologic disease has also been shown to be safe whether the patient is elderly or young and has been shown to be beneficial as it is associated with lower surgical invasiveness and less postoperative pain compared to open surgery in elderly patients [8, 9]. We also observed no surgical complications during surgery in the present series, except for 1 case of intraoperative arrhythmia and extrasystole and another case of intraoperative hypertension.…”
Section: Discussionsupporting
confidence: 59%
“…Laparoscopic surgery for benign gynecologic disease has also been shown to be safe whether the patient is elderly or young and has been shown to be beneficial as it is associated with lower surgical invasiveness and less postoperative pain compared to open surgery in elderly patients [8, 9]. We also observed no surgical complications during surgery in the present series, except for 1 case of intraoperative arrhythmia and extrasystole and another case of intraoperative hypertension.…”
Section: Discussionsupporting
confidence: 59%
“…Laparoscopic surgery was fi rst used in elderly patients in the area of gastrointestinal surgery for cholecystectomy, and many previous studies on this procedure have shown no signifi cant diff erence in the incidence of complications or duration of postoperative hospital stay between elderly and younger patients, as well as a lower incidence of complications associated with laparoscopic surgery than with open surgery (Evers et al 1994;Weber 2003). Th e very limited number of studies that have examined the use of laparoscopic surgery in elderly patients with gynaecological disease have found it to be safe; it has also been found to be safe in young patients (Jeon et al 2011;Amemiya et al 2012). To our knowledge, this is only the second study published to date that compares elderly and younger individuals who had undergone laparoscopic gynaecological surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Th us, surgeons will experience a greater number of elderly individuals undergoing surgery (Jeon et al 2011). Elderly patients typically have a high prevalence rate of comorbid conditions, such as hypertension, coronary heart disease, diabetes mellitus, pulmonary disease and central nervous system disease (Toglia and Nolan 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In women undergoing laparoscopic surgery for benign gynaecological disease, 67% aged over 70 years had comorbid disease compared with 22% of women aged 30-50 years [27]. In women undergoing surgery for ovarian cancer, 63% older than 70 years had at least three comorbidities [28].…”
Section: Comorbiditiesmentioning
confidence: 98%
“…In elderly women with advanced ovarian cancer (median age 75 years; range 70-82 years), the median number of concomitant diseases was 5 (range 1-9) [29]. The most common comorbidities were hypertension, diabetes mellitus, cardiovascular, and musculoskeletal disease [27,29].…”
Section: Comorbiditiesmentioning
confidence: 99%